Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{a+1}{a-1}+\frac{a-1}{a+1}>2\)
\(\Leftrightarrow\frac{\left(a+1\right)^2}{\left(a-1\right)\left(a+1\right)}+\frac{\left(a-1\right)^2}{\left(a+1\right)\left(a-1\right)}>2\)
\(\Leftrightarrow\frac{\left(a+1\right)^2+\left(a-1\right)^2}{\left(a-1\right)\left(a+1\right)}>2\)
\(\Leftrightarrow\frac{\left(a+1\right)^2+\left(a-1\right)^2}{a^2-1}>2\)
Với \(\left(a+1\right)^2\ge0\) mà a>1
\(\Leftrightarrow\left(a+1\right)^2>1\)
Với \(\left(a-1\right)^2\ge0\) mà a>1
\(\Leftrightarrow\left(a-1\right)^2\ge0\)
\(\Leftrightarrow\left(a+1\right)^2+\left(a-1\right)^2>1\)
Với a2\(\ge\)0 mà a>1 => a2>1 <=> a2-1>1
=> đpcm
Ta có:
\(\frac{a+1}{a-1}+\frac{a-1}{a+1}=\frac{a-1+2}{a-1}+\frac{a+1-2}{a+1}=1+\frac{2}{a-1}+1-\frac{2}{a+1}=2+\left(\frac{2}{a-1}-\frac{2}{a+1}\right)\)
Ta lại có:
\(a-1< a+1\Rightarrow\frac{2}{a-1}>\frac{2}{a+1}\)
\(\Rightarrow\frac{2}{a-1}-\frac{2}{a+1}>0\)
\(\Rightarrow2+\frac{2}{a-1}-\frac{2}{a+1}>2\)
\(\Rightarrow\frac{a+1}{a-1}+\frac{a-1}{a+1}>2\left(đpcm\right)\)
\(\frac{a+1}{a-1}+\frac{a-1}{a+1}\)\(=\frac{\left(a+1\right)^2}{\left(a-1\right)\left(a+1\right)}+\frac{\left(a-1\right)^2}{\left(a-1\right)\left(a+1\right)}\)
\(=\frac{a^2+2a+1+a^2-2a+1}{a^2-1}\)
\(=\frac{2a^2+2}{a^2-1}=\frac{2a^2-2+4}{a^2-1}=\frac{2a^2-2}{a^2-1}+\frac{4}{a^2-1}\)
\(=\frac{2\left(a^2+1\right)}{a^2+1}+\frac{4}{a^2-1}\)\(=2+\frac{4}{a^2-1}\)
a > 1 => a2 > 1 => a2 - 1 > 0 => 4/a2 - 1 dương
\(\Rightarrow2+\frac{4}{a^2-1}>2\)